Pengaruh Insentif, Pelatihan, Lingkungan, Disiplin Terhadap Kinerja Karyawan PT. Adira Multi Finance Bandar Jaya - Ana Andrizanah; I Komang Winatha; Yon Rizal (FKIP Unila, 2021)
The purpose of this study is to determine the effect of the influence of incentives, training, work environment and work discipline on the employee’s performance. The research method used in this research is descriptive method verification with ex post facto approach and survey. The population in this study is that all employees of PT. Adira Multi Finance Bandar Jaya Branch, Central Lampung and a sample of 38 respondents are determined by saturated sampling techniques. Data collection is done using a questionnaire. The collected data is processed by simple linear regression test and mulitple linear regression test. The results of the data analysis shows that there is insignificant influences on incentives, training, work environment and work discipline on employee performance.